Research on construction of public health system in China – a CiteSpace-based visualization analysis of studies published since the COVID-19 epidemic - Yuntong ZHAO; Ziyi PENG; Shuai DU; Wuqi QIU; Pei DONG; Ayan MAO (Zhongguo gonggong weisheng)
ObjectiveTo visually analyze the published studies on the public health system construction in China since the coronavirus disease 2019 (COVID-19) epidemic, and provide a reference for improving the research design in this field. MethodsUsing "public health," "public health system," "public health field," "system construction," and "planning" as keywords, we searched the China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and Wanfang Database for literature relevant to public health system construction in China published from January 2020 to April 2024. We conducted two rounds of screening and quality assessment based on inclusion and exclusion criteria, such as completeness of information and consistency with the basic study content. We used Excel software to sort and classify the included literature, and statistically analyzed the publishing institutions and research collaborations. Based on CiteSpace V software, we created a visual map of keyword co-occurrence, keyword clustering, and keyword time zones, and then analyzed and interpreted the map content. ResultsA total of 161 articles on public health construction in China were included. The authors of the articles were mainly from universities and disease prevention and control institutions. The collaborative studies published in the articles were mainly between universities and scientific research institutions, and between universities and hospitals. The main research keywords were public health, emergency management, system construction, epidemic prevention and control, capacity building, human resources, and informatization. The research hotspots mainly focused on the medical prevention and control cooperation mechanism between disease prevention and control institutions and medical institutions, the emergency management system (monitoring and early warning, emergency response, and infectious disease treatment), talent team building (talent training, staffing, talent utilization, and evaluation), financial investment mechanism, and information technology support. The main concerns were talent training, information technology construction, primary and rural public health construction, and laboratory testing capacity and equipment. The 161 studies were divided into three phases: the early, middle, and late phases of the COVID-19 pandemic. Early-phase research focused mainly on emergency management, human resources, and information technology; mid-phase research focused on collaborative governance mechanisms; and late-phase research was mostly retrospective and analytical. ConclusionsSince the COVID-19 epidemic, research on public health system construction in China has basically covered the major areas of system construction. Recently, however, the focus of research has shifted to underdeveloped areas, with more attention being paid to equity in access to public health services.